2021
DOI: 10.25165/j.ijabe.20211405.6148
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation decision model for tomato seedlings based on optimal photosynthetic rate

Abstract: Soil moisture is a major environmental factor that influences tomato growth and development. Suitable soil moisture not only increases tomato production but also saves irrigation water. In this study, an irrigation decision model was developed, which called soil moisture regulation model, for optimizing growth of tomato seedlings while saving water. The data used for modeling were collected from a multi-gradient nested experiment, in which temperature, photosynthetic photon flux density (PPFD), carbon dioxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Successive projections algorithm (SPA) is a forward feature variable selection method, that can find the most representative characteristic wavebands by analyzing collinearity between bands (Ma et al, 2022). The genetic algorithm (GA) is a method of searching for an optimal solution by simulating the natural evolution process (Wan et al, 2021). This method established the corresponding fitness function after encoding each channel, and the characteristic wavebands were obtained by methods of selection, crossover, and mutation.…”
Section: Optimal Wavelength Selectionmentioning
confidence: 99%
“…Successive projections algorithm (SPA) is a forward feature variable selection method, that can find the most representative characteristic wavebands by analyzing collinearity between bands (Ma et al, 2022). The genetic algorithm (GA) is a method of searching for an optimal solution by simulating the natural evolution process (Wan et al, 2021). This method established the corresponding fitness function after encoding each channel, and the characteristic wavebands were obtained by methods of selection, crossover, and mutation.…”
Section: Optimal Wavelength Selectionmentioning
confidence: 99%
“…High quality, efficient and intelligent cultivation of tomatoes is a current research hotspot, whereas it also faces problems such as low irrigation and fertilizer utilization and environmental pollution. Irrigation and fertilizer directly influence tomato growth and development, yield formation and fruit quality [4][5][6] . Optimizing irrigation and fertilizer management helps to sustain greenhouse tomato production, achieve the "win-win" strategy of high yield and profit maximization, and reduce environmental risks caused by irrational fertilization management practices [7] .…”
Section: Introductionmentioning
confidence: 99%
“…The system can help to obtain a precise measurement of soil moisture in the plant root zone and apply the required proportion of water at the right time. Water stress may damage metabolic processes and photosynthetic apparatuses, leading to a decrease in crop growth [23]. Ors et al [24] found that water stress conditions can permanently damage plant growth by disrupting root and stem development and by reducing the width and number of leaves.…”
Section: Introductionmentioning
confidence: 99%